DYNAMIC ERROR OF THE TEMPERATURE SENSORS WITH THE SOUNDING OF THE ATMOSPHERE - E. A. Bolelov; Yu. M. Ermoshenko; M. B. Fridzon; Yu. N. Korablev (Научный вестник МГТУ ГА)
Radiosounding of the atmosphere is an essential component constituting the base for prognostic aviation authorities. GPR scanning data are the basis for the mapping of baric topography used in the development of aviation weather forecasts. Currently, numerical methods of weather forecast have become especially popular. This is quite justified, as these methods allow to increase the accuracy of weather forecasts and these techniques represent the future. However, the era of "numerical weather prediction" will not come soon. This is primarily due to imperfect numerical forecast models, which do not provide for timeliness and reliability of weather forecasting required for aviation. However, the quality of meteorological support of aircraft flights is largely determined by the timeliness and predictability of the aviation weather forecasts. In this regard, the network of radiosounding functions require the presentation of the theoretical foundations and providing consumers with normalized metrological characteristics of the measuring system of radio sounding, methods of measurement and a reasonable assessment of the reliability of the results of sensing. A number of these problems have been resolved nowadays, however, so far the problem of estimating dynamic measurement errors in the sounding is not solved. The metrological characteristics and the dynamic error of measurement of temperature with the new temperature sensors of foreign production (NТС MFB-5000-3220), recently used in the Russian radiosondes still require the detailed studies.This article is devoted to one of the most important types of errors of radio sounding – the dynamic errors of measurement, to be precise, the dynamic error of the temperature measurement. In the article the problem of determining the value of dynamic errors of radiosondes is being solved alongside with the investigation of the role of this kind of errors when assessing the reliability of the results of the atmosphere radio sounding.